Plasma Concentration of von Willebrand Factor in Acute Myocardial Infarction - Sakai, Hiroyuki; Goto, Shinya; Kim, Jae-Young; Aoki, Naoto; Abe, Sumihisa; Ichikawa, Noriko; Yoshida, Minako; Nagaoka, Yuta; Handa, Shunnosuke (Thrombosis and Haemostasis, 2000)
Recent investigations have revealed the crucial role of von Willebrand factor (vWF) in platelet thrombus formation under flow conditions. The plasma concentrations of vWF were measured together with various hemodynamic and hemostatic parameters in 51 cases of acute myocardial infarction. In 10 randomly selected cases, the plasma concentrations and distribution of multimers vWF were serially determined after reperfusion therapy by percutaneous transluminal coronary angioplasty (PTCA). The vWF concentration at the onset of the acute myocardial infarction was significantly higher than in an age-matched control group (vWF AG: 18.7 ± 1.2 µg/ml vs. 10.3 ± 0.5 µg/ml, p = 8.43×10− (12), mean ± SE). Simultaneous determination of hemodynamic and hemostatic parameters revealed that the only two parameters that were significantly correlated with the patients` plasma vWF concentrations were their pulmonary capillary wedge pressure (PCWP) and heart rate, suggesting a relationship between hemodynamic changes induced by the onset of myocardial infarction and the vWF plasma concentrations. Serial determinations revealed that the vWF concentrations had not changed 1 h after reperfusion therapy, but that they significantly increased by 24 to 72 h. The distribution of the larger multimers of vWF also increased in the acute and subacute phase. The vWF concentration and multimer distribution normalized 14 days after the onset of the myocardial infarction. Our findings suggest that the vWF concentration increased in acute myocardial infarction patients, possibly in association with the hemodynamic deterioration that occurs in acute myocardial infarction.
Keywords: Von Willebrand factor; myocardial infarction; platelet; coronary thrombosis; PTCA